2014
DOI: 10.1136/sextrans-2013-051350
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mobility on sexual risk behaviour and HIV infection: a cross-sectional study of men who have sex with men in southern India

Abstract: ObjectivesMobility is an important factor contributing to the spread of HIV among key population at risk for HIV; however, research linking this relationship among men who have sex men (MSM) is scarce in India. This study examines the association between mobility and sexual risk behaviour and HIV infection among MSM in southern India.MethodsData are drawn from a cross-sectional biobehavioural survey of 1608 self-identified MSM from four districts of Andhra Pradesh in India, recruited through a probability-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Altogether, our results confirm the hypothesis and findings of some previous studies of different contexts that overall, risk-takers abroad are the ones who are also risk-takers at home both among MSM [116][117][118] and others 172,173 . The respondents who experienced UAI with casual partner(s) abroad in study III seemed to be social and outgoing regardless of context.…”
Section: Comparison To Previous Studiessupporting
confidence: 91%
“…Altogether, our results confirm the hypothesis and findings of some previous studies of different contexts that overall, risk-takers abroad are the ones who are also risk-takers at home both among MSM [116][117][118] and others 172,173 . The respondents who experienced UAI with casual partner(s) abroad in study III seemed to be social and outgoing regardless of context.…”
Section: Comparison To Previous Studiessupporting
confidence: 91%
“…The lack of awareness of means of self‐protection demonstrates an urgent need for the implementation of health‐related education and promotion programmes. As observed in prior research with MSM conducted in India, mobile MSM have a higher likelihood of contracting HIV ; mobility may be associated with frequent sexual activities but a weaker sense of self‐protection. Our results indicated that MBs who reported greater mobility were at a high risk of HIV infection, and special attention should be paid to this vulnerable subgroup.…”
Section: Discussionmentioning
confidence: 52%
“…First, given its universality among study participants, mobility can be viewed as being intimately connected with sex work at the destinations. Secondly, a relationship between mobility and HIV infection has been reported by multiple authors , either because mobile MBs are involved in high‐risk behaviours or because the process of mobility itself may cause the geographical spread of the disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other topics include the relationship between mobility and HIV risk,11 seroadaptive behaviours,12 sexual risk typologies in young African Americans13 and HIV couples testing in China 14…”
mentioning
confidence: 99%